Design of novel non-contact multimedia controller for disability by using visual stimulus. Issue 3 (December 2015) - Pan, Jeng-Shyang; Lo, Chi-Chun; Tsai, Shang-Ho; Lin, Bor-Shyh
Highlights: A noncontact multimedia controller is proposed to operate via visual stimuli. A wearable EEG acquisition device is developed to monitor EEG in daily life. The proposed system can effectively reduce long-term care burden. Abstract: The design of a novel non-contact multimedia controller is proposed in this study. Nowadays, multimedia controllers are generally used by patients and nursing assistants in the hospital. Conventional multimedia controllers usually involve in manual operation or other physical movements. However, it is more difficult for the disabled patients to operate the conventional multimedia controller by themselves; they might totally depend on others. Different from other multimedia controllers, the proposed system provides a novel concept of controlling multimedia via visual stimuli, without manual operation. The disabled patients can easily operate the proposed multimedia system by focusing on the control icons of a visual stimulus device, where a commercial tablet is used as the visual stimulus device. Moreover, a wearable and wireless electroencephalogram (EEG) acquisition device is also designed and implemented to easily monitor the user's EEG signals in daily life. Finally, the proposed system has been validated. The experimental result shows that the proposed system can effectively measure and extract the EEG feature related to visual stimuli, and its information transfer rate is also good. Therefore, the proposed non-contact multimedia controller exactly provides a good prototype of novel multimedia controlling scheme.